Timing of autumn migration of dendrophilous birds in the forest-steppe Trans-Urals - Tarasov V.V.; Lyakhov A.G. (Трансформация экосистем)
The article presents the results of a study of the dynamics of autumn migration of small birds obtained during their captures with mist nets in the Kurgan Oblast in 2013, 2014 and 2016. Overall, we studied 55 species and report changes in their relative abundance from late July to mid-October as well as the starting, ending and peak dates of the migration for most species. Also, we determined the sequence of their departures from the region, classified the species by the dynamics and the number of main migration waves, defined the dominant species in the captures both for the entire migration period and for its different stages. Moreover, in the article we discuss long-term changes in the timing of autumn bird migration in the forest-steppe Trans-Urals, its direction, duration of stops, timing of migration of individuals from different age and sex groups.